Over-expression in cis of the midgut P450 CYP392A16 contributes to abamectin resistance in Tetranychus urticae. (March 2022) - Papapostolou, Kyriaki Maria; Riga, Maria; Samantsidis, George-Rafael; Skoufa, Evangelia; Balabanidou, Vasileia; Van Leeuwen, Thomas; Vontas, John
Abstract: Cytochrome P450 mediated metabolism is a well-known mechanism of insecticide resistance. However, to what extent qualitative or quantitative changes are responsible for increased metabolism, is not well understood. Increased expression of P450 genes is most often reported, but the underlying regulatory mechanisms remain widely unclear. In this study, we investigate CYP392A16, a P450 from the polyphagous and major agricultural pest Tetranychus urticae . High expression levels of CYP392A16 and in vitro metabolism assays have previously associated this P450 with abamectin resistance. Here, we show that CYP392A16 is primarily localized in the midgut epithelial cells, as indicated by immunofluorescence analysis, a finding also supported by a comparison between feeding and contact toxicity bioassays. Silencing via RNAi of CYP392A16 in a highly resistant T. urticae population reduced insecticide resistance levels from 3400- to 1900- fold, compared to the susceptible reference strain. Marker-assisted backcrossing, using a single nucleotide polymorphism (SNP) found in the CYP392A16 allele from the resistant population, was subsequently performed to create congenic lines bearing this gene in a susceptible genetic background. Toxicity assays indicated that the allele derived from the resistant strain confers 3.6-fold abamectin resistance compared to the lines with susceptible genetic background. CYP392A16 is over-expressed at the same levels in these lines, pointing to cis -regulation of gene expression. In support of that, functional analysis of the putative promoter region from the resistant and susceptible parental strains revealed a higher reporter gene expression, confirming the presence of cis -acting regulatory mechanisms. Graphical abstract: Image 1 Highlights: CYP392A16 from Tetranychus urticae that metabolizes abamectin in vitro is localized in the midgut. RNAi functionally validates its role in abamectin resistance and introgressed lines retain high CYP392A16 expression levels. Reporter gene assays provide evidence for cis -regulation.